The Effect of Scientific Approach on Early Reading Ability in Early Childhood Group A at Aidil Fitri 2 Kindergarten Palembang - Sabrina, Ully; Astuti, Mardiah; Oktamarina, Lidia; Febriyanti, Febriyanti; Sartika, Indah Dwi; Atika, Nyimas (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2024)
This research provides a background for an image that students in early reading have not developed optimally. With the title of the research on